2019
DOI: 10.1063/1.5082685
|View full text |Cite
|
Sign up to set email alerts
|

In situ small-angle X-ray scattering environment for studying nanocrystal self-assembly upon controlled solvent evaporation

Abstract: We present a sample environment for the investigation of nanoparticle self-assembly from a colloidal solution via controlled solvent evaporation using in situ small-angle X-ray scattering. Nanoparticles form ordered superlattices in the evaporative assembly along the X-ray transparent windows of a three-dimensional sample cell. The special design of the sample cell allows for monitoring the superlattice formation and transformation at different stages of the assembly process during the movement of the evaporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…To observe the time‐resolved assembly of PbS nanocrystals during solvent evaporation, we used a custom‐built sample chamber allowing for in situ SAXS measurements in transmission mode . Before the sample was filled in, the chamber was evacuated and purged with helium twice to ensure oxygen‐ and water‐free environment, although at this size PbS nanocrystals were reported to exhibit stability in air .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To observe the time‐resolved assembly of PbS nanocrystals during solvent evaporation, we used a custom‐built sample chamber allowing for in situ SAXS measurements in transmission mode . Before the sample was filled in, the chamber was evacuated and purged with helium twice to ensure oxygen‐ and water‐free environment, although at this size PbS nanocrystals were reported to exhibit stability in air .…”
Section: Resultsmentioning
confidence: 99%
“…The real‐time self‐assembly of PbS nanocrystals was monitored during controlled solvent evaporation in a custom‐built chamber . Briefly, the solvent vapor chamber used for in situ SAXS measurements was equipped with two Kapton windows for the incident and scattered X‐ray beam.…”
Section: Methodsmentioning
confidence: 99%
“…[11][12][13][14][15]19 However, the GISAXS geometry is limited to the surface characterization due to small incident angles of the X-ray beam and cannot deliver information about bulk superlattice structure. In our previous studies, 21,22 we demonstrated in situ small-angle X-ray scattering (SAXS) measurements in transmission mode of the evaporative self-organization of colloidal NCs into superstructures with long range order. In this technique, the structural information on a thick nanocrystal solid can be monitored both in the solvated and dried states during the real-time in situ NC assembly.…”
mentioning
confidence: 99%
“…11,12,15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] In this study, we use a recently designed custom-made sample environment for in situ SAXS measurements in transmission mode described in detail in Ref. 21. In this chamber, the solvent in the colloidal suspension evaporates slowly (e.g., the evaporation rate is < 0.3 µl/min for heptane and < 0.2 µl/min for toluene) and the nanocrystals form highly ordered superlattices along the cell windows (Figure 1a).…”
mentioning
confidence: 99%
See 1 more Smart Citation